2018
DOI: 10.7554/elife.31656
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 regulates core and stabilizing circadian clock loops, coupling redox and timekeeping in Mus musculus

Abstract: Diurnal oscillation of intracellular redox potential is known to couple metabolism with the circadian clock, yet the responsible mechanisms are not well understood. We show here that chemical activation of NRF2 modifies circadian gene expression and rhythmicity, with phenotypes similar to genetic NRF2 activation. Loss of Nrf2 function in mouse fibroblasts, hepatocytes and liver also altered circadian rhythms, suggesting that NRF2 stoichiometry and/or timing of expression are important to timekeeping in some ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 72 publications
2
77
0
1
Order By: Relevance
“…In accordance with our study, the expression level of the Nrf2 shows circadian rhythm, and is higher at the start of inactive phase than that of the active phase in lung of mice [41]. On the other hand, both Nrf2 knockout mice and Keap1 knockout mice which is regarded as Nrf2 constitutive active mice, demonstrate disruption of circadian rhythm [42]. A Nrf2 activator, tertiary butylhydroquinone, also affects clock gene expression [42].…”
Section: Plos Onesupporting
confidence: 86%
See 1 more Smart Citation
“…In accordance with our study, the expression level of the Nrf2 shows circadian rhythm, and is higher at the start of inactive phase than that of the active phase in lung of mice [41]. On the other hand, both Nrf2 knockout mice and Keap1 knockout mice which is regarded as Nrf2 constitutive active mice, demonstrate disruption of circadian rhythm [42]. A Nrf2 activator, tertiary butylhydroquinone, also affects clock gene expression [42].…”
Section: Plos Onesupporting
confidence: 86%
“…On the other hand, both Nrf2 knockout mice and Keap1 knockout mice which is regarded as Nrf2 constitutive active mice, demonstrate disruption of circadian rhythm [42]. A Nrf2 activator, tertiary butylhydroquinone, also affects clock gene expression [42]. These reports suggest that luteolin can regulate the circadian rhythm though the Nrf2 activation.…”
Section: Plos Onementioning
confidence: 99%
“…These studies used genetic or feeding regime manipulations, including restricted feeding, calorie restriction, high fat diet, and genetic models of type 2 diabetes, and showed that changes in animal metabolic homeostasis alter the clock function in the SCN and peripheral tissues such as the liver and heart[ 57 – 61 ]. Recent studies have revealed several input mechanisms: AMP-activated protein kinase (AMPK) phosphorylates CRY1 for accelerated degradation[ 62 ], NAD + -dependent deacetylase sirtuin-1 (SIRT1) promotes BMAL1 and PER2 deacetylation[ 63 – 65 ], poly(ADP-ribose) polymerase (PARP1) ribosylates CLOCK[ 66 ], NADP + /NADPH ratio and oxidative stress regulates BMAL1/CLOCK activity that involves the redox-sensitive antioxidative transcription factor NRF2[ 67 , 68 ], hypoxia-inducible factor 1-alpha (HIF1α) regulates Per2 transcription[ 69 – 71 ], and the tumor suppressor p53 modulates Per2 both at the transcriptional and post-transcriptional levels[ 72 , 73 ]. Our work provides additional mechanistic details about how the mTOR pathway links metabolic signals to the circadian clock function.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen sulphide (H 2 S), which acts as an entraining agent and population synchroniser, is also likely to act via transient inhibition of electron transport (Sohn, Murray, & Kuriyama, ). Timekeeping, redox state and cellular function are also closely intertwined in higher eukaryotes; in the SCN, daily redox rhythms modulate the activity of potassium channels and neuronal excitability (Wang et al., ; Wible et al., ).…”
Section: Characteristics Of Metabolic Rhythmsmentioning
confidence: 99%